Parenting styles and academic achievement - Ngu, Leh Seng; Hanafi, Zahyah; Taslikhan, Muhajir (SAS Publishers, 2016)
Type of parenting style found to be influences the child's academic achievement. This study aimed to identify the type of parenting styles practiced by parents and its relationship to the academic achievement of children.They are 406 of form five students involved in this study. Researcher used "Parenting Style Scale" instrument to measure the parenting styles.The results revealed that many parents adopt authoritative parenting style and there is no significant relationship between parenting styles and their child's academic achievement.